1988
DOI: 10.1111/j.1399-3054.1988.tb09199.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of soil and atmospheric drought on photosynthesis and stomatal control of gas exchange in three coniferous species

Abstract: 1988. The effects of soil and atmospheric drought on photosynthesis and stornatal control of gas exchange in three coniferous species. -Physiol. Plant. 73: 97-104.The responses of steady-state CO, assimilation rate (A), transpiration rate (E). and stornatal conductance (&) to changes in leaf-to-air vapour pressure difference (AW) on one hand and to increasing soil drought on the other hand were examined in 2-year-old seedlings of Pseudotsuga menziesii. Pseudotsuga macrocarpa and Cedrus atlantica. Analysing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 25 publications
(22 reference statements)
4
49
0
1
Order By: Relevance
“…However, environmental conditions did not affect all the gas exchange parameters in a similar way and their evolution through time was not the same. Maximum A and E out of phase values have been also reported for three conifer species [20], suggesting a different sensitivity to pressure potential variation by stomata and mesophyll cells.…”
Section: Discussionmentioning
confidence: 87%
“…However, environmental conditions did not affect all the gas exchange parameters in a similar way and their evolution through time was not the same. Maximum A and E out of phase values have been also reported for three conifer species [20], suggesting a different sensitivity to pressure potential variation by stomata and mesophyll cells.…”
Section: Discussionmentioning
confidence: 87%
“…There is an increasing gradient of drought resistance, ranging from A. alba, from French Mediterranean areas (Aude and Eastern Pyrenees) and probably Italian provenances which are probably better adapted to drought, especially atmospheric drought [48,50,52], than northern provenances, through to A. numidica and A. cephalonica which exhibit the best adaptation via a drought avoidance strategy.…”
Section: Drought Resistancementioning
confidence: 99%
“…1c), thus supporting the postulate (Schulze, 1986) that alterations of leaf water status are not involved in the responses of A and g s to A w Analyzing the data in an A vs Ci graph (Fig. 1d, closed symbols) showed, as had already been found for other coniferous species (Guehl and Aussenac, 1987;Grieu et aL, 1988) (Terashima et al, 1988), was shown in the second phase of the experiment in which Aw was returned near its initial low level. During that phase, A recovered partially, with the data points remaining approximately on the same supply function (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…It has been proposed (Guehl and Aussenac, 1987;Grieu et al, 1988) that decreasing C0 2 assimilation in response to increasing Aw is not only due to stomatal closure, but could be, at least partially, a consequence of altered mesophyll photosynthetic capacity. However, that interpretation is not consensual (Terashima et al, 1988 (Ci) were calculated from the gasexchange data using classical equations (see Guehl and Aussenac, 1987).…”
Section: Introductionmentioning
confidence: 99%